2007
DOI: 10.1177/0013916506298800
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Physical Vulnerability and Public Perceptions of Global Climate Change in the United States

Abstract: Although there is a growing body of research examining public perceptions of global climate change, little work has focused on the role of place and proximity in shaping these perceptions. This study extends previous conceptual models explaining risk perception associated with global climate change by adding a spatial dimension. Specifically, Geographic Information Systems and spatial analytical techniques are used to map and measure survey respondents' physical risk associated with expected climate change. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
349
5
29

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 512 publications
(424 citation statements)
references
References 53 publications
(57 reference statements)
41
349
5
29
Order By: Relevance
“…Residual plots of annual rainfall (Mwanza). Leiserowitz 2006;Brody et al 2008). Consistent with previous work (see Leiserowitz 2006;Semenza et al 2008), we observed that people with higher levels of education perceive a lower risk associated with climate change.…”
Section: Multinomial Logistic Regressionsupporting
confidence: 90%
See 3 more Smart Citations
“…Residual plots of annual rainfall (Mwanza). Leiserowitz 2006;Brody et al 2008). Consistent with previous work (see Leiserowitz 2006;Semenza et al 2008), we observed that people with higher levels of education perceive a lower risk associated with climate change.…”
Section: Multinomial Logistic Regressionsupporting
confidence: 90%
“…Inconsistent with previous literature, we did not find income to be negatively associated with climate change risk perceptions as suggested by some researchers (see Leiserowitz 2006;Brody et al 2008;Semenza et al 2008) that people with higher household income will perceive a lower risk associated with global climate change. The differences between our findings and previous studies are likely due to contextual and the techniques used to establish statistical associations between the outcome and independent variables.…”
Section: Multinomial Logistic Regressioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Personal threat of climate change has also been linked to support for a range of policies to address the issue (e.g., Brody et al 2008;Zahran et al 2006). In addition to the correlational research in support of this view, a recent experimental study by Scannell and Gifford (2013) found that providing individuals with local climate information-and thus highlighting personal threat-increased their engagement with the issue.…”
Section: Introductionmentioning
confidence: 99%